Improving Outcomes with Surgical Resection and Other Ablative Therapies in HCC - Rahul Deshpande; Derek O'Reilly; David Sherlock (International Journal of Hepatology)
With rising incidence and emergence of effective treatment options, the management of hepatocellular carcinoma (HCC) is a complex multidisciplinary process. There is still little consensus and uniformity about clinicopathological staging systems. Resection and liver transplantation have been the cornerstone of curative surgical treatments with recent emergence of ablative techniques. Improvements in diagnostics, surgical techniques, and postoperative care have lead to dramatically improved results over the years. The most appropriate treatment plan has to be individualised and depends on a variety of patient and tumour-related factors. Very small HCCs discovered on surveillance have the best outcomes. Patients with advanced cirrhosis and tumours within Milan criteria should be offered transplantation. Resection is best for small solitary tumours with preserved liver function. Ablative techniques are suitable for low volume tumours in patients unfit for either resection or transplantation. The role of downstaging and bridging therapy is not clearly established.